1999
DOI: 10.1103/physrevb.60.12475
|View full text |Cite
|
Sign up to set email alerts
|

Resistive upper critical fields and irreversibility lines of optimally doped high-Tccuprates

Abstract: Received Hc2-n1.tex)We present the resistively-determined upper critical field H ρ c2 (T ) and the irreversibility lines H ρ irr (T ) of various high-Tc cuprates, deduced from measurements in 61-T pulsed magnetic fields applied parallel to the c axis. The shape of both H ρ c2 (T ) and H ρ irr (T ) depends monotonically on the anisotropy of the material and none of the samples show saturation of H ρ (T ) at low temperatures. The anomalous positive curvature, d 2 H ρ /dT 2 > 0, is the strongest in materials with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

24
143
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(168 citation statements)
references
References 27 publications
(37 reference statements)
24
143
1
Order By: Relevance
“…The resistance decreases rapidly below the zero-field transition temperature T c (H=0T)=29K, and becomes zero below the irreversibility temperature T irr (H). The white circles locate T irr and show that it is a rapid function of applied field, so that even for fields much smaller than the upper critical field (H c2 (x=0.10)~45T [11]), perfect conductivity does not occur until the temperature is well below T c (H=0T).…”
mentioning
confidence: 99%
“…The resistance decreases rapidly below the zero-field transition temperature T c (H=0T)=29K, and becomes zero below the irreversibility temperature T irr (H). The white circles locate T irr and show that it is a rapid function of applied field, so that even for fields much smaller than the upper critical field (H c2 (x=0.10)~45T [11]), perfect conductivity does not occur until the temperature is well below T c (H=0T).…”
mentioning
confidence: 99%
“…the in-plane resistivity ρ ab (T ,H ) in pulsed and d.c. magnetic fields. Previous transport studies in cuprates identified H c2 (T ) with the 'knee' at or near the top of the ρ ab (T ) curve or the temperature at which ρ ab (H ) attained a certain fraction of the normal-state value 15 . Either technique would lead to a H c2 (T ) line with a markedly different shape from that determined by the Nernst effect, for example.…”
mentioning
confidence: 99%
“…Apart from the inter-planar correlations, it is important to establish whether it is the coupling of the field to the spins or to the motion of the electrons which is responsible for the field-induced order. Clarification would permit rigorous scrutiny of the idea that the vortices in the superconductors nucleate the field-induced order, a phenomenon rather different from the Zeemaninduced pair-breaking likely to be responsible for the high-field superconductorinsulator transition characteristic of the underdoped cuprates 17,18 .The standard technique for measurement of antiferromagnetic order is neutron diffraction, the magnetic analogue of structural x-ray diffraction. In all previous experiments to characterize the field-induced order in high-temperature superconductors, the field was vertical and approximately perpendicular to the CuO 2 planes.…”
mentioning
confidence: 99%
“…Apart from the inter-planar correlations, it is important to establish whether it is the coupling of the field to the spins or to the motion of the electrons which is responsible for the field-induced order. Clarification would permit rigorous scrutiny of the idea that the vortices in the superconductors nucleate the field-induced order, a phenomenon rather different from the Zeemaninduced pair-breaking likely to be responsible for the high-field superconductorinsulator transition characteristic of the underdoped cuprates 17,18 .…”
mentioning
confidence: 99%